Fast synthetic spectral fitting for large stellar samples: a critical test with 25 bright stars of known rotation. Issue 4 (20th January 2021) - Schröder, K-P; Mittag, M; Flor Torres, L M; Jack, D; Snellen, I
ABSTRACT: This work presents and tests a reliable, but nonetheless fast, method for determining the physical parameters of large stellar samples with moderate-resolution spectra, with extensive host star–exoplanet studies in mind. The proposed strategy complements spectral synthesis for obtaining spectroscopically sensitive parameters (i.e. effective temperature and rotation velocity) through other data to keep less critical quantities fixed. We test this approach on a sample of 25 bright (4–7 mag), cool main-sequence stars, for which rotation periods are known from chromospheric activity monitoring. On the basis of good-quality (signal-to-noise ratio 70–80) Tracking and Imaging Gamma-Ray Experiment–Heidelberg Extended Range Optical Spectrograph (TIGRE–HEROS) spectra with a modest spectral resolving power of R = 21 000, we employ the fast iSpec tool. With gravities calculated and approximate metallicities taken from uvby photometry (Geneva–Copenhagen catalogue), spectral synthesis is focused on refining the crucial effective temperature. Finally, rotational velocities are fitted. However, these suffer from cross-talk with gravity and convective turbulence. We find that prescribing macroscopic turbulent velocities for most stars within 2–3 km s −1 (with 4–6 km s −1 for only our three warmest stars) and microscopic turbulent velocities within 0.7–1.5 km s −1 (turbulence increasing with effective temperature, from under 5000 K to 6300 K) results in a satisfactory match (with residuals of 2.5 km s −1 ) of the period-related, very small rotation velocities of our sample stars. With this prescription, the fast spectral synthesis method described yields effective temperatures similar to intensive atmospheric modelling of high-resolution spectra.